Emergency Psychiatric–Mental Health Nursing Interventions for Older Adults: A Systematic Review and Meta-Analysis - Marliana, Thika; Metz-Ruszkai, Szilvia; Purebl, György; Binti Osman, Suhaila; Safitri, Yunita Restu; Octavia, Lia (Chakra Brahmanda Lentera Institute, 2026)
Background: Older adults represent a highly vulnerable population in psychiatric emergency settings due to cognitive decline, multimorbidity, and psychosocial instability. Although psychiatric emergency nursing interventions are increasingly implemented, existing evidence remains fragmented and lacks comprehensive synthesis focusing specifically on nursing-led, non-pharmacological approaches in emergency contexts. The research aimed to evaluate the effectiveness of psychiatric emergency nursing interventions in reducing agitation, physical restraint use, and emergency pharmacotherapy among older adults, and to identify the most effective intervention components. Methods: This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The protocol has been submitted to PROSPERO and is currently under review. A comprehensive search was performed in PubMed, CINAHL, PsycINFO, and Scopus for studies published between January 2013 and December 2023, with the final search conducted in December 2023. A total of 1,246 records were identified; 27 studies met the inclusion criteria and were included in the meta-analysis. Risk of bias was assessed using design-appropriate appraisal tools. Data were synthesized using a random-effects model. Statistical heterogeneity was evaluated using the I² statistic, and sensitivity analyses were performed to assess robustness. Results: Psychiatric emergency nursing interventions including intensive therapeutic communication, structured de-escalation strategies, and family involvement significantly reduced agitation among older adults (pooled effect size = -0.68; 95% CI: -0.84 to -0.52; I² = 75%). These interventions were also associated with decreased use of physical restraints and emergency pharmacological management. Most randomized studies demonstrated low risk or some concerns, while non-randomized studies exhibited moderate risk of bias. Conclusion: Nursing-led psychiatric emergency interventions are effective in reducing agitation and minimizing restrictive practices among older adults in emergency settings. However, substantial heterogeneity across studies limits the certainty of evidence. These findings support the development of standardized evidence-based clinical protocols and targeted geriatric psychiatric nurse training, particularly in resource-constrained emergency systems. Further high-quality randomized trials are required to strengthen the evidence base and inform policy implementation